Protective Effect of Fucoxanthin against UVB-Induced Skin Photoaging in Hairless Mice - URIKURA, Itaru; SUGAWARA, Tatsuya; HIRATA, Takashi (Bioscience, biotechnology, and biochemistry, 2011)
Fucoxanthin, a major carotenoid in brown algae, has various beneficial effects. In this study, we evaluated the effect of topical fucoxanthin on UVB-induced skin photoaging in hairless mice. The dorsal skins were treated topically with a 0.001% fucoxanthin solution 2 h each time before UVB irradiation (5 times a week) for 10 weeks. The formation of wrinkles in UVB-irradiated skin treated with vehicle alone significantly increased, as compared with the non-irradiated control. Treatment with fucoxanthin tended to suppress UVB-induced wrinkle formation, but there was no significant difference between wrinkle formation in the control group and the fucoxanthin treatment group. However, topical treatment with fucoxanthin significantly lessened UVB-induced epidermal hypertrophy, VEGF, and MMP-13 expression in the epidermis and thiobarbituric acid reactive substances (TBARS) in the skin. These results indicate that topical treatment with fucoxanthin prevents skin photoaging in UVB-irradiated hairless mice, possibly via antioxidant and antiangiogenic effects.